Integration of a quantum scheme for key distribution and authentication within EAP-TLS protocol. (29th March 2019) - Ghilen, Aymen; Azizi, Mostafa
The extensive deployment of wireless networks has led to a significant progress in security approaches that aim to protect confidentiality. The current method for exchanging a secret key within 'extensible authentication protocol-transport layer security' (EAP-TLS) protocol is based on public key infrastructure (PKI). Although this technique remains one of the most widely implemented solution to authenticate users and to ensure secure data transmission, its security is only computational. In other words, by the emergence of the quantum computer, the existing cryptosystems will become completely insecure. Improving the contemporary cryptographic schemes by integrating quantum cryptography becomes a much more attractive prospect since its technology does not rely on difficult mathematical problems such as factoring large integers or computing discrete logarithms. Thus, we propose a quantum extension of EAP-TLS that allows exchanging a cryptographic key and authenticating a remote client with unconditional security, ensured by the laws of quantum physics. PRISM tool is applied as a probabilistic model checker to verify specific security properties for the new scheme.